UI/UX Design of The ENC Application as Electronic Nursing Care in Clinical Practice Education for Nursing Students in Hospitals. - Minanton, Minanton; Agustina, Habsyah Saparidah; Khoirunnisa, Nurfitria (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The implementation of hospital information systems in the digitalization-based era, including medical records, currently shows that there is a need for nursing education to focus on information education, including developing electronic-based practical student nursing care applications. This research aimed to design the user interface and user experience of electronic nursing documentation, named "The ENC". The ENC (electronic nursing care) with a design thinking approach. Designing the user interface (UI) and user experience (UX) used a design thinking approach consisting of empathize, define, ideate, prototype and test. Data collection was carried out at the empathize stage using content questionnaires and interviews. UI/UX design using the Figma application. Application testing with nursing student users based on predetermined scenarios. The ENC (electronic nursing care) application design uses the design thinking method to produce an application prototype that adapts to the needs of nursing students. To validate the efficacy of The ENC application, testing was conducted with nursing student users through predetermined scenarios. The design thinking approach facilitated the creation of an application prototype attuned to the specific requirements of nursing students. Following this, a comprehensive survey involving 30 nursing students was conducted to assess usability, quality, and satisfaction with the application's UI/UX, thereby capturing both positive and negative feedback. The ENC application adapts to the needs of nursing students to ease the transition from paper-based to electronic-based documentation, increase acceptance of the application, and increase its use in the clinical environment.